Available Resources of English Story Telling on Spotify to Enhance Listening Comprehension Skills - Hidayah Nor; Abdul Hair (Journal of English Language Teaching and English Linguistics, 2023)
Learning a new language encompasses various skills, including writing, reading, speaking, and listening. Developing listening comprehension abilities can be particularly challenging and requires consistent practice. An effective approach to improving listening skills is through exposure to audio storytelling. However, language learners often struggle to locate suitable content for this purpose. This study aims to identify and analyze audio storytelling resources available on the Spotify platform, specifically accessible to students. The analysis of these resources will facilitate a better understanding of their content and provide opportunities for practicing listening comprehension.The research adopts a qualitative approach, utilizing a content analysis method to evaluate the available content on Spotify. The researcher explored the platform to identify audio storytelling content and assess their potential for enhancing listening abilities. Factors such as content types, popularity, difficulty levels, and activity rates were considered during the analysis.The findings revealed three prominent channels on Spotify that specialize in audio storytelling content. These channels are popular among Spotify users, actively upload new content at least once a week, and offer content with varying difficulty levels. Each channel contains a rich collection of audio stories, encompassing grammatical and vocabulary aspects tailored to different difficulty levels, along with opportunities for exploring diverse cultures